Molecular features and genetic markers of gastrointestinal stromal tumors - N. N. Mazurenko; I. МЮ Tsyganova (Успехи молекулярной онкологии, 2015)
Gastrointestinal stromal tumors (GISTs) are the most spread mesenchymal tumors located within the gastrointestinal tract that have particular clinico-morphological, immunohistochemical and molecular characteristics. The distinguishing mark of GISTs is the presence of the cell-surface antigen CD117 (KIT receptor tyrosine kinase), identified by immunohistochemistry. GISTs consist of tumors with various activating mutations in KIT (75–80 %) or PDGFRA (5–15 %) receptor tyrosine kinases. Numerous KIT and PDGFRA mutations are associated with specific GIST morphology, histologic phenotype, metastasizing and prognosis. 10–15 % of GISTs contain KIT and PDGFRA wild type genes, some of them have driver BRAF, IGF1R or PIK3CA mutations. The other GISTs patients have familial syndromes (neurofibromatosis type 1, Carney–Stratakis syndrome, Carney triad) and contain germline mutations of NF1 or the genes coding for the succinate dehydrogenase subunits SDHA, SDHB, SDHC, and SDHD. GISTs are first and the most studied model for development of principles and methods of personalized targeted therapy of solid tumors with tyrosine kinase inhibitors.